Therapeutic Footwear Wearing Behaviors among Persons with Diabetes - นิธิชัย, นิรุชา; กนกสุนทรรัตน์, นิโรบล; ศิริพิทยาคุณกิจ, อภิญญา (Journal of The Royal Thai Army Nurses, 2019)
This descriptive research was aimed to explore therapeutic footwear wearing behaviors among persons with diabetes who received therapeutic footwear and their health belief perceptions. The sample group composed of 80 Diabetes persons who had their routine followed up visit and received therapeutic footwear at chronic cound clinic of the surgical outpatient unit of Ramathibodi Hospital. Data were analyzed using descriptive statistics, content analysis, and Spearman rank correlation coefficient. Research results and additional analysis showed that most persons with diabetes had medium to high therapeutic footwear wearing behaviors. Perceptions on risk of Diabetic foot ulcer, severity of diabetic foot ulcer, benefits of therapeutic footwear wearing were at high levels and significantly positively related to wearing therapeutic footwear behaviors (r = 0.272 p < .05, r = 0.239 p < .05, r = 0.564 p < .01, respectively), whereas perception of the obstacles for wearing therapeutic footwear was at a low level and was significantly negatively related to therapeutic footwear wearing behaviors, (r = -0.519, p < .01). These research finding can be utilized in nursing plans, especially in patients with high risk for Diabetic foot ulcer for appropriate therapeutic footwear wearing behaviors to reduce incidence of diabetic foot ulcers and amputations.